Interspecific interactions between two Tuta absoluta (Lepidoptera: Gelechiidae) larval parasitoids with contrasting life histories - Savino, V. (2017)
Interspecific interactions between two larval parasitoids of Tuta absoluta (Meyrick) with partially overlapping host niches were studied: the idiobiont ectoparasitoid Dineulophus phthorimaeae De Santis, and the koinobiont endoparasitoid Pseudapanteles dignus (Muesebeck). T. absoluta is an important pest of tomato crops worldwide, and its management could be improved by understanding the competitive interactions and potential coexistence between these two parasitoids. Firstly, a 15-min fixed time laboratory test evaluated the host-searching ability of adult D. phthorimaeae and P. dignus wasps on T. absoluta larvae. Secondly, D. phthorimaeae host discrimination against endoparasitized and non-endoparasitized hosts by P. dignus, at different adult female ages, was experimentally examined. D. phthorimaeae wasps spent significantly more time in general searching in the presence of its competitor than in its absence, but, parasitism was only effective by P. dignus. Older D. phthorimaeae wasps discriminated significantly less than young wasps between T. absoluta larvae parasitized and unparasitized by P. dignus, and an interaction took place by non-concurrent host-feeding. Intra-guild predation of P. dignus larvae by D. phthorimaeae female feeding behaviour might have a minor effect in this system. Results are discussed in the context of literature supporting diverse evidence of coexistence in other parasitoid-host systems, with implications for T. absoluta biological control.